The Impact of Organizational Safety and Health (Office Ergonomics) on Employees Productivity - Zainurol Fazli, Zainudin (2010)
This study is about the impact of Organizational Safety and Health on employee's productivity. The objective of this study was to look into the practices of Safety and Health Procedures and Regulations in the UPSI Tanjung Malim, UiTM Shah Alam and UPM Serdang. This study also attempt to determine some important of organizational safety and health issues in the organizations surveyed and to look into employees' level of understanding on Organizational Safety and Health Administration Act. This study was limited to Administrative Support Staff working in Administrative Department of the three universities and this study focused only on office ergonomics. A questionnaire was developed and distributed for the purpose of data collection. 67 percent of response rate was obtained from the 100 questionnaires that were distributed to respondents. The researchers found that more than half of the respondents were made aware of OSHA practiced by their employers which is 80.6% (54) and knows about Organizational Safety and Health (OSHA) procedures and regulations practiced by their employers. The researchers also found that mostly half of them did not do anything to address their discomfort of health problems that they experienced during their daily work activities. However, the level of understanding about OSHA practices in the three organizations is good or very good. As a general conclusion, the level of awareness on Organizational Safety and Health (OSHA) among employees in UPSI Tanjung Malim, UiTM Shah Alam and UPM Serdang is good or very good because more that half which is equivalent to 80.5% (54) of the respondents aware about what is OSHA